Study Of Services Provided to Beneficiaries of Chiranjeevi Yojana in Urban Slum of Ahmedabad City of Gujarat - Vaishali K Mehariya; Jay K Sheth; DV Bala (Medsci Publications, 2015)
Background: For achievment MDG goal of reduction of Maternal mortality Government of Gujarat has taken an iniative "Chiranjeevi Yojana"(CY) with the help of Public Private Partnership (PPP). Objective of the study was to assess health services provided by private obstetricians & perceptions of beneficiaries regarding scheme amongst the beneficiaries registered under CY. Method: A cross-sectional study by purposive sampling was conducted in 2011 in Ahmedabad Municipal Corporation among 74 beneficiaries registered under CY who delivered in February 2011 by interview method. Results: Beneficiaries in the age group of 21 to 30 were 86%. ANC visits were chargeable in 13.5% beneficiaries and 86.5% beneficiaries paid for USG examinations. In most cases IFA tablets, TT injections and Laboratory investigation were provided by nearby urban health centre (UHC) and not by the private provider. More than half (52.7%) of beneficiaries were charged for deliveries. Charge of CS deliveries was 100% with CS rate of 9.5%. Transportation charge was not provided to 98.6%beneficiaries. Conclusion: Poor awareness in beneficiaries was observed regarding what services they are entitled under CY.